2003
DOI: 10.1021/ic0301627
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nitrosyls of a Pentadentate Ligand Containing a Single Carboxamide Group:  Syntheses, Structures, Electronic Properties, and Photolability of NO

Abstract: Three iron complexes of a pentadentate ligand N,N-bis(2-pyridylmethyl)amine-N-ethyl-2-pyridine-2-carboxamide (PaPy(3)H, H is the dissociable amide proton) have been synthesized. All three species, namely, two nitrosyls [(PaPy(3))Fe(NO)](ClO(4))(2) (2) and [(PaPy(3))Fe(NO)](ClO(4)) (3) and one nitro complex [(PaPy(3))Fe(NO(2))](ClO(4)) (4), have been structurally characterized. These complexes provide the opportunity to compare the structural and spectral properties of a set of isostructural [Fe-NO](6,7) comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
91
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 57 publications
16
91
1
Order By: Relevance
“…[18,[27][28][29][30][31][32][33][76][77][78] A copper() complex was recently reported, where the carboxamido function of acetyl-uns-penp is no longer truly sp 2 hybridised and the nitrogen atom undergoes a weak interaction with the metal centre. [13] In our present work, we demonstrated that acetyl-uns-penp is capable of influencing coordination chemistry by building hydrogen bonds with hydrogen acceptors in the vicinity of the carboxamido function.…”
Section: Resultsmentioning
confidence: 99%
“…[18,[27][28][29][30][31][32][33][76][77][78] A copper() complex was recently reported, where the carboxamido function of acetyl-uns-penp is no longer truly sp 2 hybridised and the nitrogen atom undergoes a weak interaction with the metal centre. [13] In our present work, we demonstrated that acetyl-uns-penp is capable of influencing coordination chemistry by building hydrogen bonds with hydrogen acceptors in the vicinity of the carboxamido function.…”
Section: Resultsmentioning
confidence: 99%
“…[8]. This method lead, in our lab, to better results (in terms of [15,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] for Fe 3+ (NO) complexes; Refs. [15,17,18,35,[47][48][49][50][51][52] for Fe 2+ (NO); Refs.…”
Section: Comparison Of Ir Nitrosyl Bands Formed On Different Fe-samplesmentioning
confidence: 99%
“…In 2002, Patra, Mascharak and co-workers reported the NO photo-releasing properties of iron nitrosyl complexes with several carboxamide-containing pentadentate ligands [50,81].…”
mentioning
confidence: 99%
“…However, the stability of this complex in biological media is poor [81,82]. From DFT calculations, it was observed that the electronic transition that labilizes NO occurs from a bonding Fe-NO orbital with a partial carboxamide character to an antibonding Fe-NO orbital.…”
mentioning
confidence: 99%